Outcomes and predictors of mortality following periprosthethic proximal femoral fractures. Issue 2 (February 2019) - Finlayson, Graham; Tucker, Adam; Black, Nicholas D.; McDonald, Sinead; Molloy, Mary; Wilson, Darrin
Abstract: Background: Periprosthetic fractures are a well-documented, serious complication of joint arthroplasty, occurring in up to 11% of hip replacements. We examined periprosthetic femoral fractures over an 8 year period to determine the demographics, fracture pattern and management options and associated outcomes. Furthermore, we sought to determine which comorbidities resulted in increased risk of 12 month mortality after periprosthetic fractures about hip replacements Methods: A retrospective review of a prospective fracture database was conducted for the years 2007–2015. The Fracture Outcomes Research Database (FORD) was interrogated for patients aged >60 years, admitted with periprosthetic hip fracture. Radiographic and Electronic Clinical Record review was performed to classify fractures, record treatments, comorbidies and 12 month mortality. A multivariate analysis was performed to determine comorbidities that significantly increased the risk of 12 month mortality. Results: A total of 189 patients were identified. The majority were Vancouver B1 fractures (61.9%); the operations were primarily cable plating (75.1%), with a smaller number of revision arthroplasties (21.2%) and only three proximal femoral replacement (1.6%). Four patients (2.1%) died before surgery. Only 27.3% returned to their usual residence post-discharge. Overall 30-day mortality was 2.1%, and one-year mortality was 11.6%. Patients who died tended to be older. In the multivariate analysis, ASA grade III/IV and active neoplasia were significant contributors to 12 month mortality. Conclusion(s): Our 12 month mortality (11.6%) is at the lower end of existing reported literature, and serves as a benchmark for UK practice. In the multivariate analysis, only ASA grade III/IV and an active neoplastic process were significantly associated with increased risk of mortality. Whilst large, multicenter trials, utilizing standardized treatment techniques are required to fully assess risk factors for 12-month mortality, it appears that those at significant risk are elderly, frail individuals with an active malignancy.